N-acetyl-L-tryptophan attenuates hepatic ischemia-reperfusion injury via regulating TLR4/NLRP3 signaling pathway in rats - Yitong Pan; Shuna Yu; Jianxin Wang; Wanzhen Li; Huiting Li; Chen Bai; Yaxin Sheng; Ming Li; Chenchen Wang; Jiao Liu; Peitong Xie; Can Wang; et al. (PeerJ, 2021)
The aim of this study was to investigate the changes of TLR4/NLRP3 signal during hepatic ischemia-reperfusion injury (HIRI) and to verify whether N-acetyl-L-tryptophan (L-NAT) protected hepatocytes by regulating the activation of TLR4/NLRP3 signal. We have established the rat HIRI model and H2O2-induced cell damage model to simulate ischemia-reperfusion injury and detect the corresponding indicators. Compared with the sham group, Suzuki score and the level of serum ALT increased after HIRI, accompanied by an increased expression of NLRP3, ASC, Caspase-1, IL-1β, TLR4, and NF-κB. While L-NAT pretreatment reversed the above-mentioned changes. Compared with the control group, cells in the H2O2 treated group became smaller in cell volume and round in shape with unclear boundaries. Similar to the phenotypes in vivo, H2O2 treatment also induced significant increase in expression of pyroptosis-related proteins (NLRP3, ASC, Caspase-1 and IL-1β) and inflammatory factors (TLR4 and NF-κB). While L-NAT pretreatment attenuated injuries caused by H2O2. In conclusion, the present findings demonstrate that L-NAT alleviates HIRI by regulating activation of NLRP3 inflammasome, which may be related to the TLR4/NF-κB signaling pathway.